2021
DOI: 10.1186/s12888-021-03389-7
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 related poor mental health and sleep disorders in rheumatic patients: a citizen science project

Abstract: Background Patients with chronic rheumatic diseases (RDs) are more vulnerable and the containment measures related to the COVID-19 pandemic might have severe psychological consequences. We investigated the presence of and risk factors associated with poor mental health, sleep disorders among RDs during the pandemic. Methods This cross-sectional Italian citizen science project evaluated the psychological impact of the COVID-19 pandemic in patients w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…With regard to psychiatric aspects of the total sample, it is not surprising that at least mild clinically significant affective symptoms are present in about one-third of our patients being affected by inflammatory diseases and pain. This is particularly true for those with RA or SpA as reported in previous investigations by our group on different samples [ 14 , 81 ]. Similarly, increased BMI has been already found to be associated with the onset and severity of depressive symptoms as a result of impaired lipid metabolism [ 82 ], weakness of antioxidant defenses [ 83 ], and increased inflammation [ 84 ].…”
Section: Discussionsupporting
confidence: 73%
“…With regard to psychiatric aspects of the total sample, it is not surprising that at least mild clinically significant affective symptoms are present in about one-third of our patients being affected by inflammatory diseases and pain. This is particularly true for those with RA or SpA as reported in previous investigations by our group on different samples [ 14 , 81 ]. Similarly, increased BMI has been already found to be associated with the onset and severity of depressive symptoms as a result of impaired lipid metabolism [ 82 ], weakness of antioxidant defenses [ 83 ], and increased inflammation [ 84 ].…”
Section: Discussionsupporting
confidence: 73%
“…Sleeping abnormalities are commonly experienced by rheumatic patients [ 14 ]. Some studies conducted during the pandemic found that 30–40% of the participants experienced insomnia during isolation [ 9 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with RDs who were unemployed and had a lower monthly income were at a higher risk for depression than those who were employed and had a higher monthly income. Previous reports found that temporary unemployment, decrease in monthly income, and drug discontinuation owing to the pandemic were associated with reduced quality of life among patients with RDs [ 10 ] and that patients with RDs with higher anxiety due to reduced income since the pandemic experienced higher levels of stress [ 14 ]. This indirectly supports the argument that patients who are unemployed and have a lower income may be more vulnerable to depression.…”
Section: Discussionmentioning
confidence: 99%
“…As patients with RDs must adapt to their disease and comply with treatment regimens for the rest of their lives, depression is a common mental health disorder observed in this population owing to increased disease activity, suboptimal treatment adherence, reduced treatment response, and decreased quality of life [ 8 , 9 ]. Fear of health risk, stress, social isolation [ 10 ], anxiety [ 11 ], disease activity [ 12 ], physical symptoms [ 13 ], and insomnia [ 14 ] during the current pandemic can elevate the risk of depression or exacerbate depression symptoms among patients with RDs. Prior studies have reported that the unprecedented changes in the social environment caused by social distancing, restricted social gatherings, working from home, online-centered lifestyle, and quarantine during the pandemic posed serious mental health threats to patients with RDs.…”
Section: Introductionmentioning
confidence: 99%